Pendidikan Kesehatan Secara Virtual: Efektifkah Sebagai Upaya Pencegahan Terjadinya Penundaan Dalam Mengakses Pelayanan Kesehatan Ketika Mengalami Sindrom Koroner Akut - Jeki Refialdinata; Mandria Yundelfa (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Acute Coronary Syndrome (ACS) is the main cause of sudden death in a person. Sudden death due to ACS can be prevented if individuals who show symptoms of ACS immediately obtain health services. If the family (caregiver) has good knowledge about ACS, the delay can be avoided. The method of implementing health education that is safe to use during the COVID-19 pandemic is to be carried out virtually. The purpose of this study was to examine the effectiveness of virtual health education in increasing family knowledge about ACS. The research was carried out in the work area of the Andalas Public Health Center, Padang City. The type of research used is quantitative using a quasi-experimental non-equivalent control group design. The sample in this study were family members of individuals who are at high risk of experiencing ACS totaling 266 people consisting of 133 people in the case group and 133 others in the control group. The sample was selected using purposive sampling technique. Respondents' understanding of the material after health education, both in the case group and the control group, was evaluated using an instrument in the form of a questionnaire consisting of 15 questions. The data obtained from the questionnaire were analyzed statistically using the SPSS program. The results showed that virtual health education had a positive effect on respondents' knowledge of ACS in the case group compared to the control group. The results showed that there was a significant effect of health education on knowledge (p value = 0.000) of respondents in the case group. However, there was no effect in the control group (p value 0,181). The health promotion team should continue to provide health education to the public about ACS during COVID-19 pandemic using virtual media. Thus, health promotion programs can continue to be carried out without having to worry about the spread of the corona virus.